Microbiome Innovation in Agriculture: Development of Microbial Based Tools for Insect Pest Management - Qadri, Masroor; Short, Sierra; Gast, Kalani; Hernandez, Jordan; Wong, Adam Chun-Nin (Frontiers in Sustainable Food Systems, 2020)
According to the Entomological Society of America’s (ESA) recent position statement, invasive insects incur control costs of over $2.5 billion and cause economic damages to crops, lawns, forests, and pastures totaling $18 billion per year (“The Not-So-Hidden Dangers of Invasive Species” 2018). The threat of invasive crop pests to food security continues to be driven by complex dynamics of human movements, global trade activities, climate change, and changing agricultural practices. Chemical insecticides have been central to crop protection against invasive insects. However, a growing demand for reduced agricultural chemical use due to environmental and human health concerns in addition to pesticide resistance issues are fueling interests in innovative approaches to manage invasive pests. For decades, the role of microbes in pest management has been largely confined to using entomopathogens, with only a handful of microbial species being developed into bioinsecticides. The paradigm is shifting owing to the advent of high-throughput sequencing, functional omics, and gene editing technologies, which greatly accelerate microbial discovery, as well as a better understanding of microbial functions in complex communities across different habitats. There is also overwhelming evidence that symbiotic microbes play pivotal roles in shaping various insect traits. The collection of microbes associated with a given environment (both biotic and abiotic) and their collective genetic materials is termed the microbiome. In this paper, we survey the latest development in microbiome research that could be leveraged into novel management tools for agricultural insect pests (Figure 1). We first review the diverse insect traits shaped by insect-microbe associations that span nutrition, immunity, ecological interactions with natural enemy, insecticide resistance, and behavior. This is followed by a discussion on different microbiome manipulation approaches to alter pest traits, describing some of the opportunities and obstacles for each approach. We then highlight microbiomes as untapped chemical inventories to discover novel biopesticides, including plant-incorporated protectants and semiochemicals. The last topic covered is the use of beneficial microbes to improve performance of mass-reared insects for autocidal programs, including sterile insect technique and incompatible insect technique, in which we identify topics where data are limited or inconclusive for future research.